KLINIK TUMBUH KEMBANG ANAK DI KANDANGAN - Rahminy, Fatimathus Zahra; Fawzia, Irma; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The growth and development of a child is one of the most important processes for every parent. However, many children experience challenges in their growth and development, which require evaluation at a child development clinic. In Kandangan, there is currently no child development clinic that provides optimal services, and many children have negative perceptions of healthcare environments. Healthcare facilities should be places where children experience positive outcomes, such as healing, rather than negative emotions like fear. Therefore, there is a need for a clinic designed with an approach that addresses how negative perceptions of healthcare environments are formed and a concept that can transform these negative perceptions. Using the Environmental Perception Approach and Playful design concept, the aim is to create a child development clinic that changes children's perceptions into a more enjoyable and welcoming environment.